Degradation Techniques of Hemicellulose Fraction from Biomass Feedstock for Optimum Xylose Production: A Review - Budi Mandra Harahap (Universitas Brawijaya, 2020)
The utilization of xylose, one of the C-5 sugars released from hemicellulose deconstruction of biomass feedstock, is intensively studied, in particular for producing valuable fermentation products. More xylose in the initial fermentation broth is highly expected to induce more final products formed. The techniques for lignocellulose fractionation to obtain the expected xylose amount are widely developed. Nevertheless, these are slightly different from the methods for glucose production. The production of glucose is initiated by delignification to facilitate enzyme accessibility in degrading cellulose to glucose. The delignification process, however, requires harsh conditions causing further decomposition of xylose corresponded to the formation of inhibitors detected in the spent liquor of pretreatment. Hence, xylose recovery needs particular treatments and the corresponding condition. Several strategies offered attributed to xylose production involved in conventional treatment using dilute acid and other promising methods such as an autohydrolysis, solid acids, steam explosion, inorganic salt, and ionic liquid. Post-treatments by enzymatic or acid hydrolysis of xylooligosaccharides dissolved in the liquid fraction are also considered to enhance xylose recovery. This review provides such techniques and the challenges frequently arising during xylose yield optimization performed. Each method has specific benefits and drawbacks that are also addressed in this paper.